2019
DOI: 10.1111/hex.12966
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in dialysis care—A qualitative study of patients’ and health professionals’ perspectives

Abstract: Background and objective End‐stage renal disease (ESRD) affects a multitude of aspects in the patient's daily life, often entailing their own involvement in various aspects of the treatment. Although patient participation is a core health‐care value, what the concept signifies is not yet fully known. The purpose of this paper is to conceptualize patient participation in dialysis care, depicting patients’ and health‐care professionals’ perspectives. Design This explorative study employed qualitative interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(74 citation statements)
references
References 36 publications
(48 reference statements)
3
66
0
Order By: Relevance
“…In the current study, nephrologists considered self-care activities equal to patient participation, seeing self-care as a source of patient empowerment. This is in line with a Swedish study [ 33 ] which found that healthcare professionals viewed the performance of dialysis as the ultimate form of patient participation in ESRD care. Patients, however, considered the choice of having the staff run their dialysis, at certain times or continuously, as an act of participation [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, nephrologists considered self-care activities equal to patient participation, seeing self-care as a source of patient empowerment. This is in line with a Swedish study [ 33 ] which found that healthcare professionals viewed the performance of dialysis as the ultimate form of patient participation in ESRD care. Patients, however, considered the choice of having the staff run their dialysis, at certain times or continuously, as an act of participation [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with a Swedish study [ 33 ] which found that healthcare professionals viewed the performance of dialysis as the ultimate form of patient participation in ESRD care. Patients, however, considered the choice of having the staff run their dialysis, at certain times or continuously, as an act of participation [ 33 ]. This is in accordance with a broader understanding of patient participation that includes dialogue, involvement in care, mutual shared knowledge and the management of self-care [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…The principles descend from both previous studies on patient participation [6,7,[11][12][13][14][15][16][17]21] and healthcare norms, literally transpiring through F. Nightingale's momentum to provide healthcare services of high quality yet in accordance with the desires of the patient [22], to today's mutual engagement of the patient and the healthcare professionals on the patient's team by means of for example person-centred care [23].…”
Section: Development Of a Match-rank For Preference-based Patient Parmentioning
confidence: 99%
“…Healthcare professionals often recount patient participation as related mainly to being engaged in decision-making [5], while patients depict it in a broader sense, including sharing experiences and information, shared decision-making, and self-management [6]. Furthermore, patients' priorities for participation have been found to vary: the way in which and to what extent one prefers to partake can alter with, for example, type of healthcare contact and the reason for it [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for people with a long‐term illness, it is important to better understand how repeated and prolonged contact with the healthcare sector can foster conditions beneficial for patient participation. Living with end‐stage renal disease (ESRD) requires that the individual engages around the clock, for example, in repeated healthcare interactions and everyday adaptions (Årestedt, Martinsson, Hjelm, Uhlin, & Eldh, 2019). Current data suggest that about 10,000 individuals are treated for ESRD in Sweden, and 4,000 of those are patients in hemo‐ or peritoneal dialysis (Swedish Renal Registry, 2018).…”
Section: Introductionmentioning
confidence: 99%